pharmaceutical-sciences 2018
DOI: 10.4172/pharmaceutical-sciences.1000340
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Gallic Acid against Cyclophosphamide- and Cisplatin-induced Immunosuppression in Swiss Albino Mice

Abstract: Shruthi, et al.: Immunomodulatory Effects of Gallic Acid in Swiss Albino MiceGallic acid is a triphenolic acid, widely distributed in fruits, vegetables and plants and is reported to produce antioxidant, antiinflammatory, antifungal, antiviral and antitumor effects. In the present study, immunomoduatory effect of gallic acid was tested against cyclophosphamide and cisplatin; two widely used anticancer agents induced immunosuppression in Swiss albino mice. Cyclophosphamide and cisplatin are known immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
4
22
0
1
Order By: Relevance
“…Cisplatin also acts as a representative redox cycler, causing direct damage to various organs and resulting in significant weight loss [34]. In the present study, mice administered with cisplatin showed adverse effects on body weight, similar to the findings of Park et al [14] and Shruthi et al [17]. However, HemoHIM treatment groups increased the body weight, which is comparable with cisplatin-treated group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cisplatin also acts as a representative redox cycler, causing direct damage to various organs and resulting in significant weight loss [34]. In the present study, mice administered with cisplatin showed adverse effects on body weight, similar to the findings of Park et al [14] and Shruthi et al [17]. However, HemoHIM treatment groups increased the body weight, which is comparable with cisplatin-treated group.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, many reports have focused on the immunomodulatory properties of cisplatin. Cisplatin induces immunomodulatory effects through inhibiting the proliferation of peripheral lymphocytes in response to allergenic cells or mitogens, the growth of B and T cells, and interruption of chemotaxis among monocytes [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gallic acid enhanced antibody titer effects. This indicates that humoral immune response can be facilitated by gallic acid 23 . In addition, Jamaican cherry fruit also contains flavonoids in the form of flavanols in large quantities such as gallocatechin and flavonols such as quercetin in small amounts 21 .…”
Section: Discussionmentioning
confidence: 83%
“…In nature, various medicinal plants are believed to promote positive health and enhance the natural resistance of the body to various human ailments. A large number of medicinal plants have been claimed to possess immunomodulatory activities (Kumar et al, 2012;Eze et al, 2017;Ahmad et al, 2018;Shruthi et al, 2018). Medicinal plants as botanical *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%